Loop conization for the treatment of microinvasive carcinoma of the cervix. Issue 4 (1st July 2006) - Tseng, C. J.; Chang, C. C.; Tseng, C. C.; Hou, H. C.; Wang, C. B.; Chen, C. H.; Soong, Y. K.; Pao, C. C.
Abstract : The purpose of the study was to evaluate the specimen adequacy and diagnostic accuracy of loop conization in microinvasive carcinoma of the cervix. A retrospective study was conducted from 1997 to 2003 at the Colposcopic Clinic, Department of Gynecology and Obstetrics, Chang Gung Memorial Hospital, Taipei, Taiwan. Sixty-three consecutive patients with microinvasive carcinoma of the cervix receiving cold-knife conization (35 patients) or loop conization (28 patients) were included in the study. All patients underwent definitive hysterectomy. We reviewed the conization specimen together with the hysterectomied uterus to compare the two conization techniques with respect to the histopathologic interpretation and diagnostic accuracy. The mean depth of cone specimens was significantly less in the loop conization compared with cold-knife conization (1.65 versus 2.35 cm, P = 0.035). Regarding the application of conization, the loop conization was completed in a single slice in 27 patients (77.1%) and in multiple slices in 8 patients (22.9 %), in spite of encouragement to perform conization in a one-pass application when possible. However, the cold-knife specimens were invariably a single cone-shaped piece. As reviewed by microscopic examination, the rate of tissue transection was significantly higher in the loop group than in the cold-knife group (14.3% versus 0%, P = 0.04). Because of tissue transection and disorientation, pathologic evaluation of stromal status was inadequate in 11.4% (4/35) of the loop cones as opposed to none of the 28 cold-knife cones. After assessing the hysterectomy specimens, the clinical diagnoses in the loop group were downgraded in three patients compared with only one in the cold-knife group. Data from this investigation suggest that cervical cold-knife conization is superior to loop conization as a method to assess microinvasive cervical cancer.